The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/cc12594
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients requiring ventilatory support in Brazilian intensive care units: a multicenter, prospective, cohort study

Abstract: IntroductionContemporary information on mechanical ventilation (MV) use in emerging countries is limited. Moreover, most epidemiological studies on ventilatory support were carried out before significant developments, such as lung protective ventilation or broader application of non-invasive ventilation (NIV). We aimed to evaluate the clinical characteristics, outcomes and risk factors for hospital mortality and failure of NIV in patients requiring ventilatory support in Brazilian intensive care units (ICU).Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
140
13
20

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(188 citation statements)
references
References 44 publications
15
140
13
20
Order By: Relevance
“…In fact, the incidence of ARDS ranges from 1.5 cases per 100 000 [2] to nearly 79 cases per 100 000 [3], with European countries reporting a lower incidence than USA [6]. Moreover, studies from Brazil reported incidence rates ranging from 1.8 to 31 per 100 000 [7,8].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the incidence of ARDS ranges from 1.5 cases per 100 000 [2] to nearly 79 cases per 100 000 [3], with European countries reporting a lower incidence than USA [6]. Moreover, studies from Brazil reported incidence rates ranging from 1.8 to 31 per 100 000 [7,8].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…In fact, the incidence of ARDS ranges from 1.5 cases per 100 000 [2] to nearly 79 cases per 100 000 [3], with European countries reporting a lower incidence than USA [6]. Moreover, studies from Brazil reported incidence rates ranging from 1.8 to 31 per 100 000 [7,8].Although the overall survival rate is improving [9,10], there is a notable difference when considering in-hospital mortality over several observational studies [2][3][4][8][9][10][11]. This may be explained by differences in risk factors, availability of diagnostics, ability to recognise ARDS and some selection biases affecting clinical trials [12].…”
mentioning
confidence: 99%
“…Unequal access to health care was one of the factors to explain the results. 12,31 This study stands out for including a specific population of patients that has become more numerous. The data was collected consecutively and in a short time interval, minimizing fluctuations in diagnosis and treatment that may occur when there are very long periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…8 The epidemiological characteristics of ARF may be influenced by regional aspects. 11,12 Endemic diseases, mainly infectious, are relevant for solid organ transplants. 13 However, contemporary data from emerging countries regarding this complication in renal transplant patients are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Dünya genelinde insidansı 1.5-79/100.000 olarak bildirilmekle birlikte, Avrupa ülkelerinde bu oran Amerika Birleşik Devletleri (ABD)'den daha düşüktür (2,3,6) . Brezilya'da 2013 tarihli yapılan çok merkezli bir çalışmada, bu oran 100.000'de 1.8 ile 31 bulunmuştur (7,8) . Ancak bu çalışmalar daha çok erişkin yaş grubunu kapsamakta olup, pediyatrik yaş grubu için insidans verileri tam olarak bilinmemektedir (9) .…”
Section: Introductionunclassified